Negative Plant-Soil Feedback Driven by Re-assemblage of the Rhizosphere Microbiome With the Growth of Panax notoginseng - Luo, Lifen; Guo, Cunwu; Wang, Luotao; Zhang, Junxing; Deng, Linmei; Luo, Kaifeng; Huang, Huichuan; Liu, Yixiang; Mei, Xinyue; Zhu, Shusheng; Yang, Min (Frontiers in Microbiology, 2019)
There is a concerted understanding of the accumulation of soil pathogens as the major driving factor of negative plant-soil feedback (NPSF). However, our knowledge of the connection between plant growth, pathogen build-up and soil microbiome assemblage is limited. In this study, significant negative feedback between the soil and sanqi (Panax notoginseng) was found, which were caused by the build-up of the soil-borne pathogens Fusarium oxysporum, F. solani, and Monographella cucumerina. Soil microbiome analysis revealed that the rhizospheric fungal and bacterial communities were changed with the growth of sanqi. Deep analysis of the phylum and genus levels corroborated that rhizospheric fungal Ascomycota, including the soil-borne pathogens F. oxysporum, F. solani, and especially M. cucumerina, were significantly enriched with the growth of sanqi. However, the bacteria Firmicutes and Acidobacteria, including the genera Pseudomonas, Bacillus, Acinetobacter and Burkholderia, were significantly suppressed with the growth of sanqi. Using microbial isolation and in vitro dual culture tests, we found that most isolates derived from the suppressed bacterial genera showed strong antagonistic ability against the growth of sanqi soil-borne pathogens. Interestingly, inoculation of these suppressed isolates in consecutively cultivated soil could significantly alleviate NPSF. In summary, sanqi growth can suppress antagonistic bacteria through re-assemblage of the rhizosphere microbiome and cause the accumulation of soil-borne pathogens, eventually building negative feedback loops between the soil and plants.